Poverty Reduction Strategies and Environment : A Review of 40 Interim and Full Poverty Reduction Strategy Papers (PRSPs) - Bojo, Jan; Reddy, Rama Chandra (World Bank, Washington, DC, 2014)
This review systematically assesses the focus of Poverty Reduction Strategy Papers (PRSPs) on environment-related issues. A total of 40 Interim and full PRSPs from countries in Africa, Latin America and Eastern Europe, the Middle East, Central and East Asia are reviewed. Four major questions: are posed: (i) What issues of environmental concerns and opportunities are identified in the PRSPs?; (ii) To what extent are poverty-environment causal links analyzed?; (iii) To what extent are environmental management responses and indicators put in place as part of the poverty reduction efforts?; and (iv) To what extent has the design and documentation of the process allowed for mainstreaming the environment? The review finds:: There is considerable variation across countries in the degree of mainstreaming: from a high score of 2.2 (Mozambique) to a low of 0.3 (Sao Tome Principe). Scores indicate the approximate level of attention given to environmental matters in the PRSPs. Some variation across countries is legitimate and to be expected, but there is no reason to believe that the lower scoring countries are free from concerns of environmental health and natural resources degradation linked to poverty. Finally, it should be recalled that a PRSP is only the written expression of an underlying and still emerging process of participation and implementation. What ultimately matters are the results on the ground, which cannot be evaluated across 40 countries at this point in time.